My rainbow - Neal, Trinity; Neal, DeShanna (Kokila, 2020)
"A dedicated mom puts love into action as she creates the perfect rainbow-colored wig for her transgender daughter, based on the real-life experience of mother-daughter advocate duo Trinity and DeShanna Neal"--